Living with Hemodialysis Due to Chronic Kidney Disease: A Phenomenological Study of Quality of Life - Maria Magdalena Dwi Wahyuni; Marni Marni; Shinta Lisa Purimahua; Theresia Rosilvada Nazario Lamatokan; Fahira Marsanda Alkatiri (Media Publikasi Cendekia Indonesia, 2026)
Patients with chronic kidney disease undergoing hemodialysis experience significant changes in quality of life, including physical, psychological, spiritual, and social aspects. The therapy leads to physical limitations, loss of autonomy, and reduced self-efficacy, which may impair patients’ ability to manage their condition and increase the risk of stress, depression, and complications. This study aimed to explore patients’ experiences and identify self-efficacy-related factors affecting quality of life among hemodialysis patients at Prof. Dr. W. Z. Johanes Kupang Hospital. A qualitative phenomenological approach was employed using in-depth interviews with 10 informants. Data were collected using unstructured interview guides, supported by audio recordings and field notes, and analyzed using the Stevick-Colaizzi-Keen method. Findings indicated that, physically, most patients reported bodily lightness, improved sleep quality, and increased ease in daily activities following routine hemodialysis; however, some continued to experience dizziness, pain, and unstable physical conditions. These physical changes were associated with patients’ self-efficacy, where improved conditions increased confidence in managing daily activities and treatment, while persistent symptoms reduced confidence in controlling their health condition. Psychologically, patients initially experienced anxiety, which decreased with adaptation and acceptance. Spiritually, patients showed increased religious devotion as a coping mechanism, while socially, patients maintained interactions with family and their environment, contributing to sustained support. These findings indicate that physical condition, psychological adaptation, spiritual coping, and social support are key factors influencing patients’ self-efficacy. Although hemodialysis necessitates complex changes in quality of life, the integration of emotional, spiritual, and social support helps patients in the process of acceptance and adaptation.